Karakterisasi Struktur Mikro dan Sifat Mekanik Paduan Al-Mg-Si Hasil Squeeze Casting Setelah Perlakuan Homogenisasi - Lestari, Venty (Manufaktur: Publikasi Sub Rumpun Ilmu Keteknikan Industri, 2025)
Al–Mg–Si aluminum alloys are widely utilized in engineering applications due to their low density, excellent corrosion resistance, and mechanical properties that can be modified through heat treatment. This study investigates the effect of homogenization on the microstructure and hardness of Al–Mg–Si alloys produced by the squeeze casting process. The experimental procedure involved alloy melting, squeeze casting at 76 MPa using preheated metal molds, followed by homogenization at 400 °C for 4 hours. Microstructural characterization was performed using optical microscopy to examine the dendritic morphology and measure the secondary dendrite arm spacing (SDAS). Mechanical properties were evaluated through Vickers microhardness and Rockwell macrohardness testing. The results show that homogenization increases the SDAS from 32.59 μm to 36.88 μm and decreases the volume fraction of interdendritic phases from 15.51% to 13.57%. Furthermore, microhardness decreased from 50.22 VHN to 38.58 VHN, while macrohardness decreased from 54.60 HRE to 46.64 HRE. These reductions are attributed to the partial dissolution of Mg₂Si precipitates into the aluminum matrix during homogenization. Overall, this research provides valuable insight into the optimization of initial heat treatment parameters for Al–Mg–Si alloys produced by squeeze casting. The findings highlight the role of homogenization in improving microstructural uniformity and preparing the alloy for subsequent deformation processes such as cold rolling and extrusion, particularly for structural components used in mining and heavy transportation industries.